(untitled) (Studia austriaca, 2015)
This paper tries to map out the political poetics of Peter Handke’s Die Lehre der Saint-Victoire (1980). Handke’s text is shown to emulate Cézanne’s painting technique of associating coloured patches with the harmonious whole of an image, a procedure that accords with Theodor Adorno’s aesthetics after Auschwitz. The stab this paper takes at fleshing out Handke’s political aesthetics leads to the critical question as to whether this is simply aestheticism revamped.